Revitalization training for TPQ through the Asset Based Community Development (ABCD) approach - Siti Toyibah (Universitas Pendidikan Indonesia, 2025)
TPQ is a non-formal educational institution that plays a crucial role in disseminating Islamic teachings, particularly in aspects aimed at enhancing the understanding and comprehension of the Qur'an. This community service adopts a qualitative approach, utilizing a case study method integrated into Asset-Based Community Development (ABCD)-based Community Service Program (KKN) activities. The community service site is located in Klepu hamlet, Planjan sub-district, Kapanewon Saptosari, Gunungkidul regency, Yogyakarta Special Region. The primary objective of this community service is to reactivate TPQ activities in the location, which were previously halted due to a limited number of teachers. As part of a revitalization effort, a Training of Trainers (ToT) program was designed to equip local teenagers with basic teaching competencies and enable them to take on the role of TPQ teachers. A total of 10 teenagers aged 14 to 18 were purposively selected based on their interest, involvement in religious activities, and potential. The training program focused on skill utilization through the provision of materials, microteaching, preparation of teaching tools, and the formation of teaching teams. The results showed that the ABCD approach was effective in exploring local assets and creating community-based solutions. Learning guides were successfully developed, and the majority of participants demonstrated basic teaching skills. Two youth teaching teams were also formed to support the sustainability of TPQ activities. Abstrak TPQ merupakan lembaga pendidikan non formal yang berperan penting dalam menyebarkan ajaran Islam terutama pada aspek yang bertujuan untuk memperdalam bacaan dan pemahaman Al-Qur'an. Pengabdian ini mengadopsi pendekatan kualitatif dengan metode studi kasus yang diintegrasikan dalam kegiatan Kuliah Kerja Nyata (KKN) berbasis Asset-Based Community Development (ABCD). Lokasi pengabdian terletak di Padukuhan Klepu, Kalurahan Planjan, Kapanewon Saptosari, Kabupaten Gunungkidul, Daerah Istimewa Yogyakarta. Tujuan utama pengabdian ini adalah mengaktifkan kembali kegiatan TPQ dilokasi tersebut yang sebelumnya terhenti akibat keterbatasan jumlah tenaga pengajar. Sebagai upaya revitalisasi, program Training of Trainers (ToT) dirancang untuk memberdayakan remaja setempat agar memiliki kompetensi dasar mengajar dan mampu mengambil peran menjadi pengajar TPQ. Sebanyak 10 remaja berusia 14 hingga 18 tahun dipilih secara purposif berdasarkan minat, keterlibatan dalam kegiatan keagamaan, dan potensi yang dimiliki. Program pelatihan difokuskan pada pendayagunaan kemampuan melalui pemberian materi, microteaching, penyusunan perangkat ajar, dan pembentukan tim pengajar. Hasil pengabdian menunjukkan bahwa pendekatan ABCD efektif dalam menggali aset lokal dan menciptakan solusi berbasis komunitas. Panduan pembelajaran berhasil disusun, mayoritas peserta menunjukkan keterampilan dasar mengajar, dan dua tim pengajar remaja terbentuk untuk mendukung keberlanjutan kegiatan TPQ. Kata Kunci: asset based community development; Kuliah Kerja Nyata; ToT; TPQ